2018
DOI: 10.3390/su10020368
|View full text |Cite
|
Sign up to set email alerts
|

Energy Recovery from the Organic Fraction of Municipal Solid Waste: A Real Options-Based Facility Assessment

Abstract: During the last years, due to the strict regulations on waste landfilling, anaerobic digestion (AD) of the organic fraction of municipal solid waste (OFMSW) is increasingly considered a sustainable alternative for waste stabilization and energy recovery. AD can reduce the volume of OFMSW going to landfill and produce, at the same time, biogas and compost, all at a profit. The uncertainty about the collected quantity of organic fraction, however, may undermine the economic-financial sustainability of such plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 36 publications
0
30
0
2
Order By: Relevance
“…Elbeshbishy et al [42] concluded that the inoculum obtained from a digester treating municipal wastewater sludge was superior to the inoculum obtained from a digester treating food waste. Lignocellulosic fibers are often present in the organic fraction of MSW; therefore, the microorganisms and enzymes present in the sludge were likely to get adapted to a lignocellulosic substrate [43]. The combined inoculation can possibly support nutrient enrichment that is very important for the anaerobic digestion process.…”
Section: Biogas Productionmentioning
confidence: 99%
“…Elbeshbishy et al [42] concluded that the inoculum obtained from a digester treating municipal wastewater sludge was superior to the inoculum obtained from a digester treating food waste. Lignocellulosic fibers are often present in the organic fraction of MSW; therefore, the microorganisms and enzymes present in the sludge were likely to get adapted to a lignocellulosic substrate [43]. The combined inoculation can possibly support nutrient enrichment that is very important for the anaerobic digestion process.…”
Section: Biogas Productionmentioning
confidence: 99%
“…Entretanto, as condições de fermentação podem afetar este padrão (KOROLEVA, 1991;GARROTE et al, 2001;FARNWORTH, 2005 De acordo com muitos pesquisadores (GUPTA et. al., 2019;RANIERI et. al., 2018) o desperdício de alimentos não só tem uma associação direta com a crise econômica, mas também envolve desperdício de recursos como terra, água que são utilizados na produção dos mesmos.…”
Section: Análise Estatísticaunclassified
“…Moreover, one-stage or two-stage processes can be differentiated. In a one-stage system, all biochemical reactions take place in one reactor, while a two-stage system consists of two reactors [28].…”
Section: Anaerobic Digestion Technologymentioning
confidence: 99%